The global prevalence of peptic ulcer in the world: a systematic review and meta-analysis - Salari, Nader; Darvishi, Niloofar; Shohaimi, Shamarina; Bartina, Yalda; Ahmadipanah, Melika; Salari, Hamid Reza; Mohammadi, Masoud (Springer, 2021)
Peptic ulcer is one of the most common diseases of the gastrointestinal tract, which, if not addressed, can increase mortality in different communities. As regards the results of various studies around the world that have reported different prevalence, the aim of this study was to determine the overall prevalence of peptic ulcer in the world through systematic review and meta-analysis. In this systematic review and meta-analysis, articles focused on the prevalence of peptic ulcer were searched in the Scopus, Embase, Web of Science, PubMed and Science Direct, Google Scholar, Magiran, Irandoc, and Scientific Information Database databases, without time limit until April 2020. To analyze the eligible studies, the random effects model was used, and the heterogeneity of the studies was investigated using the I2 index. The prevalence of peptic ulcer in the world in 21 studies with total sample size 788,525 in age range of 17–82 years was obtained as 8.4% (95% CI 5–13.7). According to the results from meta regression, the prevalence of peptic ulcer in the world decreased with an increase in sample size and increased with an increase in study years and age of participants in the study of the prevalence of peptic ulcer in the world. It was found that these differences were also statistically significant (P < 0.05). In conclusion, it is stated that due to the 8.4% prevalence of peptic ulcer, health system policy makers need to prevent and treat this disease through investigating the effective factors.